Influence of extrusion of corn and broken rice on energy content and growth performance of weaning pigs. (3rd March 2016) - Liu, Hua; Wan, Haifeng; Xu, Shengyu; Fang, Zhengfeng; Lin, Yan; Che, Lianqiang; Li, Jian; Li, Yong; Su, Xiang; Wu, De
Abstract: Two experiments were conducted to study the effects of extrusion on the energy content of corn and broken rice and on growth performance of weaning pigs. In experiment 1, 24 barrows (28 days old, 7.28 ± 0.90 kg body weight (BW)) were used to compare the effects of extrusion of corn and broken rice on the values of digestible energy (DE) in weaned pigs. The DE content in extruded corn (17.45 MJ/kg dry matter (DM)) was significantly greater ( P < 0.05) by 5.54% compared with that in corn (16.48 MJ/kg DM), while no significant difference in DE content was observed between extruded broken rice (17.66 MJ/kg DM) and broken rice (17.76 MJ/kg DM). In experiment 2, 120 weanling pigs (21 days old, 5.76 ± 0.07 kg BW) were used to evaluate the influence of substitution corn and extruded corn by different proportions of raw and extruded broken rice on growth performance of pigs. The inclusion of broken rice in the diets improved ( P < 0.05) growth performance of pigs during the first week and the 2 weeks post‐weaning but not thereafter. However, there was no significant difference in growth performance between treatments in other periods. Overall, this study indicates that feeding weaning pigs with broken rice has beneficial results.